K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 10 2021

\(x^2+2x+1-16=\left(x+1\right)^2-4^2=\left(x+1-4\right).\left(x+1+4\right)=\left(x-3\right).\left(x+5\right)\)

18 tháng 10 2021

\(x^2+2x+1-16=\left(x^2+2x+1\right)-4^2=\left(x+1\right)^2-4^2=\left(x+1-4\right)\left(x+1+4\right)=\left(x-3\right)\left(x+5\right)\)

7 tháng 8 2023

a) \(x^4+8x+63\)

\(=x^4+4x^3+9x^2-4x^3-16x^2-36x+7x^2+28x+63\)

\(=x^2\left(x^2+4x+9\right)-4x\left(x^2+4x+9\right)+7\left(x^2+4x+9\right)\)

\(=\left(x^2+4x+9\right)\left(x^2-4x+7\right)\)

7 tháng 8 2023

c) \(\left(x^2+2x+7\right)+\left(x^2-2x+4\right)\left(x^2+2x+3\right)\left(1\right)\)

Ta có : \(x^3-8=\left(x-2\right)\left(x^2+2x+4\right)\)

\(\Rightarrow x^2+2x+4=\dfrac{x^3-8}{x-2}\)

\(\left(1\right)\Rightarrow\left[\left(\dfrac{x^3-8}{x-2}+3\right)\right]+\left(x^2-2x+4\right)\left[\left(\dfrac{x^3-8}{x-2}-1\right)\right]\)

\(=\left[\left(\dfrac{x^3-3x-14}{x-2}\right)\right]+\left(x^2-2x+4\right)\left[\left(\dfrac{x^3-2x-5}{x-2}\right)\right]\)

\(=\dfrac{1}{x-2}\left[x^3-3x-14+\left(x^2-2x+4\right)\left(x^3-2x-5\right)\right]\)

9 tháng 11 2021

56B

57B

58B

9 tháng 11 2021

56.B

57.B

58.B

8 tháng 9 2023

a) \(x^2-y^2-3x+3y\)

\(=\left(x-y\right)\left(x+y\right)-3\left(x-y\right)\)

\(=\left(x-y\right)\left(x+y-3\right)\)

b) \(2x+2y-x^2+y^2\)

\(=2\left(x+y\right)-\left(x^2-y^2\right)\)

\(=2\left(x+y\right)-\left(x-y\right)\left(x+y\right)\)

\(=\left(x+y\right)\left(2-x+y\right)\)

c) \(x^2-16+y^2+2xy\)

\(=x^2+y^2+2xy-16\)

\(=\left(x+y\right)^2-16\)

\(=\left(x+y+4\right)\left(x+y-4\right)\)

8 tháng 9 2023

a) \(x^2-y^2-3x+3y\)

\(=\left(ax+y\right)\left(ax-y\right)-3.\left(x-y\right)\)

b) \(2x+2y-x^2+y^2\)

\(=2\left(x+y\right)-\left(x+y\right)\left(x-y\right)\)

c) \(x^2-16+y^2+2xy\)

\(=\left(x+y\right)\left(x-y\right)+2xy-16\)

Bạn thử xem lại đề câu d nhé.

undefinedundefined

Cảm ơn ạ.

 

 

25 tháng 11 2023

\(x^2-y^2+2x+1\\=(x^2+2x+1)-y^2\\=(x+1)^2-y^2\\=(x+1-y)(x+1+y)\)

24 tháng 10 2021

\(=\left(x+1-y\right)\left(x+1+y\right)\)

1 tháng 7 2021

`x^2+2x+1-y^2+2y-1`

`=(x^2+2x+1)-(y^2-2y+1)`

`=(x+1)^2-(y-1)^2`

`=(x+1+y-1)(x+1-y+1)`

`=(x+y)(x-y+2)`

Ta có: \(x^2+2x+1-y^2+2y-1\)

\(=\left(x+1\right)^2-\left(y-1\right)^2\)

\(=\left(x+1-y+1\right)\left(x+1+y-1\right)\)

\(=\left(x-y+2\right)\left(x+y\right)\)

20 tháng 1 2022

\(=\left(x+4\right)^2\)

20 tháng 1 2022

\(x^2+8x+16=\left(x+4\right)^2\)

26 tháng 5 2017